Evaluation of the effectiveness of the ethics & civilization course based on the cipp model: An exploratory factor analysis - Musaiyadah Ahmadun; Muzalifah Monil; Nur Ilma Ambo; Masnih Mustapa; Sharifah Sari Datu Asal; Siti Nurhafizan Panglima (Penerbit KUIS, 2024)
Evaluation is a comprehensive data collection procedure that provides an initial assessment of the effectiveness of a program or curriculum. As a result, the purpose of this study is to examine the efficiency of the ethics and civilization course for UiTM Kota Kinabalu Sabah branch students using the CIPP model. This study is entirely quantitative, involving survey methodologies and questionnaire procedures. As respondents, 150 students from ethics and civilization courses participated. Cronbach's Alpha reliability and Exploratory Factor Analysis were used to assess the data descriptively (EFA). Since of outliers in the normalcy analysis, three respondents were eliminated from this study. Cronbach's Alpha is 0.952, which is above 0.70 as a result of the achieved normality value. Meanwhile, the Exploratory Factor Analysis (EFA) results show four factors with Elgen values in excess of 1.0 and KMO values (KaiserMeyer-Olkin) of 0.942 ≥ 0.6, indicating that variable items in the evaluation of the efficiency of the ethics and civilization course are intercorrelated. We identified a new factor that influences the evaluation of the efficiency of the ethics and civilization course as a result of the exploratory factor analysis (EFA) test. Following that, the Bartlett test is significant (Chi Square 6745.895, p < 0.05). This study included no exclusions, and all loading factor values were found to be greater than 0.05. As a result, the overall findings suggest that the items for evaluating ethics and civilization courses may be measured and answered the study's objectives. A total of 45 items have been validated and are suitable for measuring the success of CIPP-based ethics and civilization courses.